Spinoza and the irrelevance of biblical authority - Preus, James S. (James Samuel), 1933-2001. (Cambridge ; New York : Cambridge University Press, 2001)
"Spinoza's Theological Political Treatise (1670) is a landmark both in democratic political theory and in the history of biblical interpretation. Spinoza championed liberty of thought, speech and writing by discrediting the Bible as the standard for truth and a source of public law. Applying a new historical criticism, he showed that biblical teaching and law were irrelevant for a modern pluralist state and its intellectual life."--Jacket.
1. Spinoza versus the interpreters -- 2. Rationalism unleashed: Ludwig Meyer's new hermeneutic -- 3. Disengagement on the right -- 4. The liberal engagement: reason, usage, history -- 5. Starting over: Spinoza's naturalized Bible.
Includes bibliographical references (pages 212-224) and index.
Keywords: Spinoza, Benedictus de, -- 1632-1677 -- Religion; Spinoza, Benedictus de, -- 1632-1677.; Bible -- Criticism, interpretation, etc. -- History -- 17th century